Financial analysis of small hospitals in the state of Pernambuco from 2009 to 2015 - Feitosa, Daize Kelly da Silva; Santos, Isadora Sabrina Ferreira dos; Souza, Kaio Flávio Freitas de; Rodrigues, Bárbara Letícia Silvestre; Barreto, Isabel de Jesus Brandão; Ribeiro , Erlene Roberta (Seven Editora, 2023)
This article presents the results of a research that aimed to evaluate the economic and financial performance of the Hospital Units qualified in the National Policy of Small Portiers Hospitals (HPP) in the state of Pernambuco, from 2009 to 2015. In order to discuss the implications of the results for the financial sustainability of the units, indicating possible alternatives. The survey data were obtained from a sample of 59 small hospitals registered in the National Health Establishments Registration System (CNES), through the System Financial Limits of Control Medium and High Complexity (SISMAC) and Information Systems Hospital and ambulatory (SIA and SIH). These secondary data were analyzed by the Consumer Price Index (IPCA). Data analysis showed a significant loss of financial capacity of the studied hospitals and significant differences between the reported amounts of revenues and performance over the years. Showing the need to point out possible strategies redirection of resources or change the service profile of these units and analyze the feasibility of HPP policy. DOI:https://doi.org/10.56238/sevened2023.004-042